2001
DOI: 10.1073/pnas.041614198
|View full text |Cite
|
Sign up to set email alerts
|

FKBP12, the 12-kDa FK506-binding protein, is a physiologic regulator of the cell cycle

Abstract: FKBP12, the 12-kDa FK506-binding protein, is a ubiquitous abundant protein that acts as a receptor for the immunosuppressant drug FK506, binds tightly to intracellular calcium release channels and to the transforming growth factor ␤ (TGF-␤) type I receptor. We now demonstrate that cells from FKBP12-deficient (FKBP12 ؊/؊ ) mice manifest cell cycle arrest in G1 phase and that these cells can be rescued by FKBP12 transfection. This arrest is mediated by marked augmentation of p21(WAF1͞CIP1) levels, which cannot b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 35 publications
2
94
0
2
Order By: Relevance
“…However, there is considerable debate regarding the role of FKBP12 in TGF-␤ signaling, since many members of FKBP are found to be expressed ubiquitously. Therefore, it is still unclear which isoform of FKBP is involved in TGF-␤ signaling in T cells (51)(52)(53)(54). In the absence of TGF-␤1 there could be disequilibria of TGF-␤ type I receptorassociated FKBPs, resulting in leaky Ca 2ϩ release channels.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is considerable debate regarding the role of FKBP12 in TGF-␤ signaling, since many members of FKBP are found to be expressed ubiquitously. Therefore, it is still unclear which isoform of FKBP is involved in TGF-␤ signaling in T cells (51)(52)(53)(54). In the absence of TGF-␤1 there could be disequilibria of TGF-␤ type I receptorassociated FKBPs, resulting in leaky Ca 2ϩ release channels.…”
Section: Discussionmentioning
confidence: 99%
“…3) Modulation by TWD1 is gene-specific, as the related Arabidopsis proteins FKBP12 (28,42) and ROF1/FKBP59 (62) have only slight effects on PGP1-mediated IAA transport compared with TWD1 when coexpressed with PGP1 in yeast. Surprisingly, coexpression of TWD1 in yeast versus protoplast and mammalian cells showed opposite effects on PGP1 activity (inhibition in yeast and stimulation in HeLa cells), suggesting that plant-specific components might be absent in the unicellular eukaryote S. cerevisiae.…”
Section: Discussionmentioning
confidence: 99%
“…6B). Furthermore, Arabidopsis FKBP12, which represents the most basic FKBP, consisting essentially just of the cis,trans-peptidylprolyl isomerase domain, and which functions as a cell cycle regulator (42), reduced PGP1-mediated IAA efflux (measured as increased IAA retention) only slightly compared with TWD1 (Fig. 6C).…”
Section: Modulation Of Pgp1-mediated Iaa Export By Twd1 Is Specific Amentioning
confidence: 99%
“…Studies in FKBP12 -/-knockout mice have shown that the FKBP12-FK506 complex is also affecting the expression of cell cycle proteins. An increase in expression of p21 in FKBP12 -/-knockout mice led to G1 cell cycle arrest (125). This mechanism may account for the antiproliferative effect observed in VSMCs (122).…”
Section: Sirolimus Analoguesmentioning
confidence: 99%